Identification of nuclear tau isoforms in human neuroblastoma cells. - Loomis, P A (1990)
The tau proteins have been reported only in association with microtubules and with ribosomes in situ, in the normal central nervous system. In addition, tau has been shown to be an integral component of paired helical filaments, the principal constituent of the neurofibrillary tangles found in brains of patients with Alzheimer disease and of most aged individuals with Down syndrome (trisomy 21). We report here the localization of the well-characterized Tau-1 monoclonal antibody to the nucleolar organizer regions of the acrocentric chromosomes and to their interphase counterpart, the fibrillar component of the nucleolus, in human neuroblastoma cells. Similar localization to the nucleolar organizer regions was also observed in other human cell lines and in one monkey kidney cell line but was not seen in non-primate species. Immunochemically, we further demonstrate the existence of the entire tau molecule in the isolated nuclei of neuroblastoma cells. Nuclear tau proteins, like the tau proteins of the paired helical filaments, cannot be extracted in standard SDS-containing electrophoresis sample buffer but require pretreatment with formic acid prior to immunoblot analysis. This work indicates that tau may function in processes not directly associated with microtubules and that highly insoluble complexes of tau may also play a role in normal cellular physiology.